SISTEM INFORMASI BERBASIS WEB PEMBUKAAN REKENING DAN DEPOSITO PADA BANK PEMBIAYAAN RAKYAT SYARIAH ALMASOEM - Nelian Mayhana; Muthmainnah Muthmainnah; Seliwati Seliwati (Universitas Nusa Cendana, 2022)
In banking activities, customers datas that is managed and stored by the bank, including the management of bank products such as savings accounts and time deposits. However, the recording of customer data at the ALMASOEM Sharia People's Financing Bank has not been computerized so that managing customer data takes a long time, causing the service to be less effective and efficient. The purpose of this study is to build a website-based information system for opening a savings and time deposit account at BPRS ALMASOEM. With this information system, it is easier for customer service to manage and serve customers quickly and precisely. This design uses a prototype method where users and developers play an active role in developing the system, while for information data collection by field observations, interviews, literature studies and systems approach. Website built using Laravel framework, PHP as programming language and MySQL database